Pengaruh Pendekatan Matematika Realistik dan Saintifik terhadap Kemampuan Berpikir Kritis dan Motivasi Belajar Siswa Sekolah Dasar - Triwidayati, Nanik; Sunardi; Budiastra , A.A. Ketut (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Mathematics learning is often considered difficult by students, so an effective approach is needed to improve students' critical thinking skills and learning motivation. This study aims to compare the effect of realistic mathematics learning approaches and scientific approaches on critical thinking skills and learning motivation of fifth grade students at Kebonsari 04 Elementary School, Jember Regency. This study used a quasi-experimental method with a treatment by levels design. The population of this study was fifth grade students consisting of two classes, VA and VB, with a total of 56 students selected through a simple random sampling technique. The instruments used in this study were critical thinking ability tests and learning motivation questionnaires. Data analysis was carried out using descriptive statistics, two-way ANAVA tests and Tukey's advanced tests. The results showed significant differences in the critical thinking skills of students who took realistic mathematics learning compared to the scientific approach, both in students with high and low learning motivation. The realistic mathematics approach was more effective in improving students' critical thinking skills, especially for those with high learning motivation. However, the scientific approach still made a positive contribution to developing students' scientific abilities. Keywords: realistic mathematics, learning motivation, scientific learning